DYNAMICS OF MARXISM BEFORE AND AFTER THE DIGITAL ERA - Richie Desandri; Aiko Chya Iswandari; Annisa Hatimah; Graciella Valencia S.; Indy Kumala Chandra (Faculty of Social and Political Sciences Universitas Kristen Indonesia, 2021)
This paper explains the role of the mass media. In this digital era, almost all people know or use this media to receive or seek various information, which is undoubtedly unlimited. In this digital era, everything is advanced from technology increasingly being developed over time—speed ​​in its delivery from the source to the broader community. Without limitation, the information can be spread among countries—the large variety of media platforms available. Now, of course, the media are also a political tool. Not left behind in the discussion of this paper regarding the policies of Marxism.